Pelatihan Penggunaan Quizizz untuk Menunjang Pembelajaran Kepada Guru di MTS Bait Al Makmur - Afni Nia Sari; Sawitri, Elvira; ., Ilmawati (CV. ITTC INDONESIA, 2024)
The impact of the rapid development of information technology, especially in the field of education, has provided additional media in the teaching and learning process, both in teaching media and in learning evaluation1. Through gamification techniques, learning can be made more fun and innovative. However, there are still many teachers who have not been able to utilize information technology-based media. From a preliminary survey conducted by this service team on 23 Mts Bait Al Makmur teachers, it appears that only 1 teaching staff or 10 percent knew about gamification-based learning media in the form of Quizizz. The implementing team successfully carried out service activities aimed at all Mts Bait Al Makmur teaching staff for 2 days1. Of the 23 teachers who took part in the training process for using Quizizz, it was found that from the evaluation results of the implementation of this service it was found that 100% of the teachers were able to operate the Quizizz learning media. As many as 100 percent understand the existing features, and 100 percent also want to use Quizizz media as a tool for learning evaluation media2. Apart from that, students also expect teachers to use this Quizizz in every learning evaluation activity2.